Phosphorus loss in surface runoff from soils with different soil test phosphorus ratings - Anjan Bhatta; Rishi Prasad; Debolina Chakraborty; Dexter B. Watts; Henry A. Torbert (Agrosystems, Geosciences & Environment, 2025)
Abstract Phosphorus (P) loading from farmland to water bodies through surface runoff is a major water quality concern. Soil test P (STP) methods developed for fertilizer recommendations are commonly used for estimating environmental P loss. This research evaluated the relationship between P concentration in runoff and STP concentrations determined by different methods (water‐soluble P, Mehlich‐1 [M1], and Mehlich‐3 [M3]) and quantified the differences in P loads in runoff from soils having distinct STP levels. Artificial rainfall simulations (RS) were conducted at four sites (1, 2, 3, and 4), having mean M1‐P values of 143, 236, 28, and 5 mg kg−1, respectively. Runoff samples were analyzed for dissolved reactive P (DRP) and total P (TP). The correlation between DRP and TP concentrations with M1 and M3 was similar in direction, but M3 had a greater correlation coefficient and was reliable for estimating environmental P loss from Coastal Plain soils. Among the four sites, cumulative DRP and TP loadings (118.4 and 232.3 g ha−1) from the first RS at site 2 with the highest M1 values were significantly higher than the other three sites (range: 3.48–37.5 g ha−1 for DRP and 6.03–83.1 g ha−1 for TP). Similarly, site 2 had the highest loading for both DRP and TP (123.5 and 194.8 g ha−1) during the second RS. No statistical differences were found between the first and second RS for both DRP and TP loads, indicating rainfall events of similar intensity occurring 24 h apart produced the same amount of P loss in runoff.